Exploring The Preference and Interest for Information Communication Technology (ICT) Usage Among Students of Allama Iqbal Open University - Babar Hussain Shah (PJDOL, 2023)
This research study was conducted to discover use of ICT in Distance Education by exploring interest and preference of ICT between students of rural and urban background at Allama Iqbal Open University Islamabad Pakistan. The study was aimed to establish the differences between urban and rural students’ interest and preference of ICT in general across the university. T